Ketika Sisa Letusan Gunung Api Menjadi Komoditi Wisata: Analisis Risiko Obyek Wisata Lava Tour Merapi Yogyakarta - Helfi Agustin; Muchamad Rifai; Suryo Ediyono (LPPM Hang Tuah Pekanbaru, 2022)
The rest of the eruption of Mount Merapi in Yogyakarta, was modified by the local community into a natural museum and managed to commemorate the terrible natural disaster that had occurred as a tourism commodity. The purpose of this study is to determine the security conditions and how the risk control has been carried out by Lava Tour tourist destinations. This research is a case study in a lava tour destination located at Mount Merapi which is still active in Yogyakarta D.I Province. Data were collected by observation using Hazard Identification and Risk Assessment (HIRA) sheets and the As Low As Reasonably Practicable (ALARP) concept, and also in-depth interviews. There were six informants who were selected purposively. The results of the identification of hazards in the Lava Tour area include rocky and sandy roads, close to cliffs, the Rest of My Treasure Museum which is in an unsafe condition. cliff fence, lack of warning signs. The safety risk assessment at Lava Tour tourist sites is two extreme risk, five high risk, and two moderate risk. Controls that have been carried out include briefings, signs, Standard Operation Procedures for driving, and personal protective equipment, First Aid training in Accidents and Emergency First Aid. The risk is still tolerable because tourism activities are opened based on the active status of Mount Merapi. Recommendations for control efforts are made by making handrails on stairs and providing boundaries for entry and exit for tourists, repairing cliff fences, diverting roads for tourist jeeps, increasing routine human resource training, public toilets and providing polyclinics.